Applications of spatial light modulators in Raman spectroscopy - Sinjab, Faris; Liao, Zhiyu; Notingher, Ioan (SAGE, 2019)
Advances in consumer display screen technologies have historically been adapted by researchers across the fields of optics as they can be used as electronically controlled spatial light modulators (SLMs) for a variety of uses. The performance characteristics of such SLM devices based on liquid crystal (LC) and digital-micro-mirror device (DMD) technologies in particular has developed to the point where they are compatible with increasingly sensitive instrumental applications, for example Raman spectroscopy. SLMs provide additional flexibility, from modulation of the laser excitation (including multiple laser foci patterns), manipulation of microscopic samples (optical trapping) or selection of sampling volume (adaptive optics or spatially offset Raman spectroscopy), to modulation in the spectral domain for high-resolution spectral filtering or multiplexed/compressive fast detection. Here, we introduce the benefits of different SLM devices as a part of Raman instrumentation, and provide a variety of recent example applications which have benefited from their incorporation into a Raman system.